Carboplatin restricts peste des petits ruminants virus replication by suppressing the STING-mediated autophagy - Zhang, Rui; Hu, Zhanying; Wei, Dingcheng; Li, Ruizhe; Li, Yanmin; Zhang, Zhidong (Frontiers in Veterinary Science, 2024)
Peste des petits ruminants virus (PPRV) is a morbillivirus that causes the acute and highly pathogenic infectious disease peste des petits ruminants (PPR) in small ruminants and poses a major threat to the goat and sheep industries. Currently, there is no effective treatment for PPRV infection.Here, we propose Carboplatin, a platinum-based regimen designed to treat a range of malignancies, as a potential antiviral agent. We showed that Carboplatin exhibits significant antiviral activity against PPRV in a cell culture model. The mechanism of action of Carboplatin against PPRV is mainly attributed to its ability to block STING mediated autophagy. Together, our study supports the discovery of Carboplatin as an antiviral against PPRV and potentially other closely related viruses, sheds light on its mode of action, and establishes STING as a valid and attractive target to counteract viral infection.